2013
DOI: 10.1111/arcm.12060
|View full text |Cite
|
Sign up to set email alerts
|

Portable X‐Ray Fluorescence Spectroscopy of Pictographs: A Case Study From the Lower Pecos Canyonlands, Texas

Abstract: We evaluate the effectiveness of non-destructive portable X-ray fluorescence spectroscopy (pXRF) for elemental analysis of pictographs at 10 sites in the Lower Pecos Canyonlands of Texas. Considerations and limitations of pXRF analysis are discussed to inform future research. We found that manganese and iron minerals were the main constituents of black and red paints, respectively. However, 40 pXRF measurements from 31 images tested at 41VV75 and 41VV76 did not contain manganese, suggesting charcoal pigment-th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 35 publications
0
18
1
Order By: Relevance
“…Similarly, a naturally spalled flake of sandstone rock shelter with applied and natural pigmentation from the Kimberley region of northwestern Australia (Figure ) was included in this experiment due to the potential of dating rock surfaces to establish an age for the associated rock art (Sohbati et al., ). pXRF is becoming routinely used in situ to analyze rock art pigments (Roldán et al., ; Olivares et al., ; Huntley et al., ; Koenig et al., ) and site taphonomy (Huntley, ; Ogburn, Sillar, & Sierra, ). Our experiment demonstrated that this type of in situ analysis can induce luminescence in the rock surface itself, especially on the “fresh” unexposed grains as discussed earlier.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a naturally spalled flake of sandstone rock shelter with applied and natural pigmentation from the Kimberley region of northwestern Australia (Figure ) was included in this experiment due to the potential of dating rock surfaces to establish an age for the associated rock art (Sohbati et al., ). pXRF is becoming routinely used in situ to analyze rock art pigments (Roldán et al., ; Olivares et al., ; Huntley et al., ; Koenig et al., ) and site taphonomy (Huntley, ; Ogburn, Sillar, & Sierra, ). Our experiment demonstrated that this type of in situ analysis can induce luminescence in the rock surface itself, especially on the “fresh” unexposed grains as discussed earlier.…”
Section: Discussionmentioning
confidence: 99%
“…To distinguish between inorganic, mineral-based pigments and PyC pigments, we analyzed the paintings in situ using a handheld portable X-ray fluorescence (HHpXRF) spectrometer. This technique has proven effective in the study of rock art primarily because it is noninvasive and provides qualitative/semi-quantitative data on chemical elements in the paints (Koenig et al 2014; Newman and Loendorf 2005; Roldán et al 2010; Rowe et al 2011). The method is especially useful for discriminating between mineral-based and carbon-based pigments, and thus for identifying specific paintings that could potentially be 14 C dated (Beck et al 2013; Koenig et al 2014; Rowe et al 2011).…”
Section: Methodsmentioning
confidence: 99%
“…This technique has proven effective in the study of rock art primarily because it is noninvasive and provides qualitative/semi-quantitative data on chemical elements in the paints (Koenig et al 2014; Newman and Loendorf 2005; Roldán et al 2010; Rowe et al 2011). The method is especially useful for discriminating between mineral-based and carbon-based pigments, and thus for identifying specific paintings that could potentially be 14 C dated (Beck et al 2013; Koenig et al 2014; Rowe et al 2011). While there has been controversy surrounding the use of HHpXRF for quantitative analyses of archaeological materials (Shackley 2010), our goal was simply to establish whether manganese or iron concentrations in paints were above the natural background levels of the bedrock.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The energy of any given secondary XRay is characteristic of a specific element, allowing qualitative identification of elements present in a sample. In addition, the detector also counts the number of secondary X-Ray from the sample, allowing quantitative elemental concentrations to be determined [17][18][19].…”
Section: X-ray Fluorescencementioning
confidence: 99%